Relevance and Role of Mediclaim in Actual Life: The Evolution of Insurance and Its Impact on Modern Life (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The word insurance truly mentions security. Security against life, heath, family, vehicle, homes, shops, etc. In earlier years, there was no need to this kind of thing for the protection. I am talking about days of our grandfathers or may be even before that. The life was so great and slow, nothing to worry about any future, would involve in their daily occupational jobs like farming and living life in their own way.